Zadovoljstvo bolnikov v primarnem zdravstvu - Gorenak, Irena (Zdravstveno varstvo, 2011)
Background: Patient-health care provider relationship and communication, and functioning of the health centrećs appointment system are the factors that influence the level of patient satisfaction with the health care services provided. This study was undertaken to study these factors and apply theoretical knowledge to the case of the health centre in Šmarje pri Jelšah, Slovenia. The main objective was to determine which of the factors studied have a significant influence on patient satisfaction with health care servicesprovided by the institution studied. Methods: This anonymous questionnaire-based study involved 225 individuals who attended the health centre clinics in June 2007. The data collected were analysed using descriptive statistics, factor analysis, co-relational analysis and regressionanalysis. The questionnaire was tested using the Cronbachćs alpha test, which confirmed the reliability of the research instrument.
Keywords: bolniki; osnovno zdravstvo; zadovoljstvo; zdravstveni domovi